Determination of ascorbic acid in Navel and Valencia oranges content grown in syrian Lattakia city - طنوس, نعمه; زينب صارم (Latakia University Journal -Medical Sciences Series, 2024)
Vitamin C is one of the vitamins play vital roles for human health. Because human body is not able to make it, it is very necessary to get vitamin C from foods. Orange is one of the best sources of vitamin C. However, vitamin C concentration in oranges may be affected by different factors. The aim of this study was to determine ascorbic acid concentration in Navel and Valencia oranges grown in different areas in Lattakia city, during different stages of maturity and using two analytical methods. The results obtained from this study showed that both of growth area and the stages of maturity had a statistically significant effect on ascorbic acid concentration in studied oranges, while the cultivation difference and the analytical method didn´t have any significant impact on its concentration.